Some heavy metals in the flesh of chub, Squalius cephalus, from Karakaya Dam Lake (Malatya, Turkey) - Dusukcan, Mustafa (C M B Assoc, 2018)
This research aimed to find out the levels of Iron (Fe), Zinc (Zn), and Cupper (Cu) in the flesh of Chub (Squalius cephalus) and in the Karakaya Dam Lake water in which they live. The findings were evaluated in terms of the risk of consuming of this fish as human food. In addition, the changes of the heavy metal level of fish with weight, length and sex of them. The accumulation factor for each metal was also found. The level of heavy metals in the flesh of fish were found higher than that in the water. The level of heavy metals changed with the weight, length and sex of fish. The results were compared with acceptable values for heavy metals given by FAO/WHO to detect whether the flesh of chub has any risk for consumption as human food.
Keywords: Karakaya Dam Lake; Chub; Squalius cephalus; Iron; Zinc; Cupper